MODEL PENGEMBANGAN DESA PUSAT PERTUMBUHAN PADA KECAMATAN PERBATASAN NEGARA DI KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT - Irfan Setiawan; Nawawi Nawawi; Muhammad Baharuddin Zubakhrum Tjenreng; Rahmawati Sururama; Dedi Kusmana (Jurnal Ilmu Pemerintahan Widya Praja, 2025)
The development of growth center villages in border areas is an important strategy in improving community welfare and equitable development. This study aims to analyze the development model of growth center villages in the Border District, Sanggau Regency, West Kalimantan Province, with a focus on Entikong Village and Balai Karangan Village. This study uses a qualitative descriptive approach, this study identifies the main factors that support village growth, such as accessibility, infrastructure, economic potential, public services, and government policy support. The results of the study show that Entikong Village has a strategic advantage as a State Border Crossing Post (PLBN), while Balai Karangan Village is developing as a local economic center with good connectivity. The proposed growth center village development model is based on the 4M approach, namely Developing trade potential, Improving basic infrastructure, Strengthening village institutions, and Improving the quality of public services. The implementation of this model is expected to accelerate the economic growth of border villages and create more inclusive and sustainable development.